The neutron moderated detector and groundbased cosmic ray modulation studies - Stoker, P. H.; Raubenheimer, B. C. (1985)
Reports appear on modulation studies with the neutron monitor without lead. Some of these studies cast doubt on the reliability of this detector. The stability of the neutron moderated detector (NMD) at Sanae, Antarctic is discussed. The barometric coeficient of the 4NMD for epoch 1976 appears not to differ statistically from the 0.73%/mb of the 3NM64. The monthly averaged hourly counting rate of our 4NMD and 3NM64 correlates very well (correlation coefficient: 98%) over the years from 1974-1984, with the 4NMD showing a 8% larger long term modulation effect than the 3NM64, indicating a difference in sensitivities of the two detectors. From this difference in sensitivities spectra of ground level solar proton events and modulation functions of Forbush decreases are deduced.